2022
DOI: 10.1038/s41598-022-05989-z
|View full text |Cite
|
Sign up to set email alerts
|

Extensive oceanic mesopelagic habitat use of a migratory continental shark species

Abstract: The identification of movement and behaviour patterns, as well as inter- and intra-population connectivity is crucial in order to implement effective and functional management and conservation measures for threatened migratory species such as tope (Galeorhinus galeus). Yet, previous studies struggled to elucidate clear and consistent movement and depth usage patterns of adult tope in the Northeast Atlantic, suggesting a high plasticity in the migration and behaviour. We deployed pop-up satellite archival tags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…depths ranging from 200 -1000 m) houses communities of macrozooplankton and micronekton (Irigoien et al, 2014;Sutton et al, 2017) which occur in localized biomass peaks below the sunlit waters (Bianchi et al, 2013). As mid-trophic level organisms, many species in these communities link primary and microbial production with higher trophic levels, including megafauna (Lehodey et al, 2010;Choy et al, 2016;Bode et al, 2021;Schaber et al, 2022). Due to their nocturnal feeding migrations to surface waters, mesopelagic organisms also play an active role in the biological carbon pump (Davison et al, 2013;Irigoien et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…depths ranging from 200 -1000 m) houses communities of macrozooplankton and micronekton (Irigoien et al, 2014;Sutton et al, 2017) which occur in localized biomass peaks below the sunlit waters (Bianchi et al, 2013). As mid-trophic level organisms, many species in these communities link primary and microbial production with higher trophic levels, including megafauna (Lehodey et al, 2010;Choy et al, 2016;Bode et al, 2021;Schaber et al, 2022). Due to their nocturnal feeding migrations to surface waters, mesopelagic organisms also play an active role in the biological carbon pump (Davison et al, 2013;Irigoien et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While there are reported examples of Pacific halibut conducting rapid vertical excursions throughout the water column between 200 -600 m, which were also interpreted as a foraging behavior (Loher and Seitz 2006;Seitz et al 2011), these rapid rises have never reported at the depths observed here (600 to 1000 m). It is possible that Atlantic halibut are distributed along the continental slope during fall and winter to feed on cephalopods or mesopelagic species, as documented in other migratory top predators (Schaber et al 2022, Skomal et al 2021). An additional possible explanation for this behavior may be exploration-related movements up and down the shelf slope and using vertical movements to aid in transportation or navigation (Hunter et al 2003;Gleiss et al 2011).…”
Section: Putative Spawning and Other Specific Vertical Movementsmentioning
confidence: 99%
“…Hutchison et al reported increased foraging behaviour, such as increased swimming distance and speed, with more sharp turns and changing swimming depth in animals exposed to between 0.3 and 14 µT [36]. | Interaction with migratory behaviour Benthic elasmobranchs as R aja clavata, Galeorhinus galeus and Mustelus asterias are known to migrate over long distances up to hundreds km per year [71]–[75]. Migrating elasmobranchs have been shown to orient using the inclination, intensity and angle of the magnetic field [23] Therefore, they might be hindered during migration when crossing a SPC if the characteristics of the geomagnetic field are altered by the emitted EMF.…”
Section: Hazard Identificationmentioning
confidence: 99%